National survey of fibrinogen concentrate usage for post‐partum hemorrhage in Japan: Investigated by the Perinatology Committee, Japan Society of Obstetrics and Gynecology. Issue 8 (27th May 2015) - Makino, Shintaro; Takeda, Satoru; Kobayashi, Takao; Murakami, Maki; Kubo, Takahiko; Hata, Toshiyuki; Masuzaki, Hideaki
Abstract Aim The aim of this study was to provide basic documents applicable to studying the usefulness of administering fibrinogen concentrate to patients with massive post‐partum hemorrhage. We investigated the usage of fibrinogen concentrate at training institutions for specialist physicians of the Japan Society of Obstetrics and Gynecology. Material and Methods The subjects were women who required fibrinogen concentrate for hemostasis of post‐partum hemorrhage during the period between April 2008 and March 2013. The underlying diseases, obstetric disseminated intravascular coagulation scores, blood loss, amount of blood transfusion, dose of fibrinogen concentrate administered, and plasma fibrinogen levels before and after the administration of fibrinogen concentrate were retrospectively investigated. Results Ninety‐nine (98.0%) patients survived and two died after taking fibrinogen concentrate. Of the surviving 99 cases, the average amount of blood loss at the time of initial fibrinogen administration and total blood loss was 3559 ± 2103 mL and 4562 ± 3198 mL, respectively. The dose per administration was 3 g, and the plasma fibrinogen level before the initial administration of fibrinogen concentrate was 70.5 mg/dL, thereafter increasing to 187.0 mg/dL. The increase in the fibrinogen level was 32.9 mg/dL/g of fibrinogen concentrate. It was less than 150 mg/dL after the first administration of fibrinogen concentrate only in patients with amniotic fluid embolism and patients with atonic bleeding showed the smallest increase in fibrinogen per gram of fibrinogen concentrate. No adverse events, including thromboembolism, were reported. Conclusion The results indicated the increase in blood fibrinogen levels to, on occasion, be insufficient even with fibrinogen concentrate use; however, this survey may support the safety and usefulness of fibrinogen concentrate for PPH.